Implementation of the Make A Match Model in Islamic Education Learning to Improve Student Learning Outcomes at SD Negeri Lamreh Aceh Besar - Erlianti; Eva Satriana (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to apply the make a match model of Amanah material to improve student learning outcomes. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were grade III students of SD Negeri Lamreh Aceh Besar. The data for this study were obtained through observation, learning outcome tests, and interviews with students and teachers. The data analysis techniques used in this study were qualitative and quantitative descriptive analysis. The results showed that there was a significant increase in student learning outcomes after the application of the Make A Match model. The average pretest score of students was 55, while the posttest score increased to 85, with a t-count value (6.82) greater than the t-table (2.04), which indicates that the Make A Match model can improve student learning outcomes. Therefore, the Make A Match learning model has proven effective in improving students' understanding of Amanah material in grade III of SD Negeri Lamreh Aceh Besar. This study is expected to be a reference for teachers in choosing the right method to improve student learning outcomes.